Nucleotide-binding oligomerization domain 1 (NOD1) regulates microglial activation in pseudorabies virus infection - Sun, Xiuxiu; Jin, Xinxin; Lin, Zhengdan; Liu, Xi; Yang, Junjie; Li, Li; Feng, Helong; Zhang, Wanpo; Gu, Changqin; Hu, Xueying; Liu, Xiaoli; Cheng, Guofu (Veterinary research (Paris), 2024)
The primary cause of viral encephalitis (VE) is invasion of the central nervous system (CNS) by the virus, which leads to neuroinflammation and poses a significant threat to global public health. Microglia, as CNS-resident macrophages, play a crucial role in neuroinflammation and are often identified as the preferred target for the prevention or treatment of VE. In this study, we used pseudorabies virus (PRV)-induced VE in mice and pigs as a model to investigate the regulation of microglial responses during viral encephalitis and explored the mechanism of microglial activation. Cellular experiments revealed that microglial activation was accompanied by cell migration, characteristic morphological changes, phagocytosis, inflammatory cytokine production, and antigen presentation. Transcriptome analysis revealed that genes related to inflammation in PRV-infected BV2 cells were significantly enriched. The expression of the NOD1 gene in BV2 cells was significantly increased during PRV infection, after which NOD1 in BV2 cells was silenced by siRNA and overexpressed via a plasmid. NOD1 was found to be involved in the secretion of cytokines in BV2 cells by regulating the MAPK/NF-κB signalling pathway. Mouse and pig experiments have shown that NOD1 is involved in the secretion of cytokines by microglia by regulating the MAPK/NF-κB signalling pathway during PRV infection.